Improving health services for street children in selected areas of Pune city - N Jamdade, Vanita (International Journal of Nursing Research, 2023)
Health is recognized as one of the basic rights of every child. Macro level challenges continue to mar the attempts made to solve the multi dimensional problems of street children. The government, civil and international bodies in India has been striving to fulfill the obligations stated in our policies and in the CRC. They are a result of increasing poverty and unemployment, increased migration of families, broken families, neglect, abuse, riots and violence, armed conflicts, natural and man-made disasters, decreasing resources in rural areas, and the attraction of cities. Aim: To assess the health status of the street children from selected areas of Pune city. Health status was assessed on the basis of nutritional assessment. Methods: A total of 100 samples, from children of age between 6-12 years were selected by using non probability convenient sampling technique. The developmental tool comprises of physical examination like anthropometric measurement like pulse rate, respiration rate, temperature, blood pressure, height, weight, systematic assessment of physical parameters, and nutritional assessment. Statistical package for Social Scientists (SPSS/PC+) computer package was used for data entry and analysis. Indices of nutritional status that is weight- for- age, height- for- age, weight- for- height were calculated using the WHO child growth standard. Results: The study findings revealed that there was a prevalence of stunted, underweight and wasted children. Out of 31% stunted growth, 04% of street children are severely wasted and 20% of street children are wasted. 7% of the street children are severely underweight and 28% of the street children are underweight.